2021
DOI: 10.1021/acsnano.1c06403
|View full text |Cite
|
Sign up to set email alerts
|

Interdigitated Three-Dimensional Heterogeneous Nanocomposites for High-Performance Mechanochromic Smart Membranes

Abstract: Mechanochromic smart membranes capable of optical modulation have great potential in smart windows, artificial skins, and camouflage. However, the realization of high-contrast optical modulation based on light scattering activated at a low strain remains challenging. Here, we present a strategy for designing mechanochromic scattering membranes by introducing a Young's modulus mismatch between the two interdigitated polydimethylsiloxane phases with weak interfaces in a periodic threedimensional (3D) structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Note that the electromechanical stretching of the photonic organogels was directly affected by the symmetrical expanding actuations of the DEA with the contraction of thickness. In recent studies where similar mechanochromic systems were investigated, [ 70,73,76,78,79 ] the organogels exhibited hexagonal lattice structures. However, in contrast to the uniaxial deformation of the HCP lattice observed in these studies, here, the HCP lattice structure of the electrically stretchable nano organogels with circular compliant facing electrodes was symmetrically expanded along both the horizontal and vertical directions during the color change process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the electromechanical stretching of the photonic organogels was directly affected by the symmetrical expanding actuations of the DEA with the contraction of thickness. In recent studies where similar mechanochromic systems were investigated, [ 70,73,76,78,79 ] the organogels exhibited hexagonal lattice structures. However, in contrast to the uniaxial deformation of the HCP lattice observed in these studies, here, the HCP lattice structure of the electrically stretchable nano organogels with circular compliant facing electrodes was symmetrically expanded along both the horizontal and vertical directions during the color change process.…”
Section: Resultsmentioning
confidence: 99%
“…[2,43,[70][71][72] Nevertheless, the wavelengthtuning mechanism of such electrically stretchable organogels is not well understood yet. Although recent reports have comprehensively illustrated the uniaxial mechanical stretchinginduced color change mechanism of similar hydrogels, [73][74][75][76][77][78][79][80] a deeper understanding of electrically stretchable chromonic organogel systems, in comparison with mechanical stretching mechanochromic systems, is required. However, elucidating the electrical mechanochromic processes involved in electrically stretchable and variable nanostructures, presents notable technical challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these effects, Chen et al reported periodic 3D structures composed of two interdigitated PDMS phases with different Young's modulus. Under strain, numerous nanogaps emerged between the phases acting as light scattering centers, rendering a high-contrast mechanical modulation of the light transmittance [149] (Figure 6d).…”
Section: Optomechanical Systems Based On Light Scattering Modulationmentioning
confidence: 99%
“…Transparent Components: Mechanochromic (MC) window, which is composed of mechanoresponsive optical materials, can switch its solar optical properties in response to mechanical strain. [18,92] The strain can reconfigure the surface morphologies or deform internal structures of the mechanoresponsive materials, which would tune the solar scattering/reflecting characteristics of the materials, resulting in varied solar transmittance. Based on the working principle, three categories of MC windows are reviewed in this section, that is, wrinkling-based, delamination bucklingbased, and kirigami structure-based.…”
Section: Mechanical-driven Materialsmentioning
confidence: 99%